1998
DOI: 10.1021/jo981467j
|View full text |Cite
|
Sign up to set email alerts
|

Sch 217048:  A Novel Cyclodepsipeptide with Neurokinin Antagonist Activity

Abstract: Neurokinins (NK), a family of 9-11 amino acid peptides, trigger a variety of inflammatory responses. 1,2 The most well characterized neurokinins, namely substance P, NKA, and NKB, are involved in a variety of responses including pain transmission, neurogenic inflammation, bronchoconstriction, and vasodilation. The peptides act

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 7 publications
1
12
1
Order By: Relevance
“…5), were isolated and identified based on comparison of their retention times and HRESIMS and MS/MS fragmentation patterns to standards in our in-house database (El-Elimat et al 2013). The NMR data for the compounds were also consistent with those reported in the literature (Hegde et al 1998(Hegde et al , 2001El-Elimat et al 2017). Additionally, the same compounds were identified in cultures of G618, G833, and G834, all grown on PDA, and analyzed by in situ sampling analysis using a droplet-LMJ-SSP coupled to an UPLC-high-resolution mass spectrometry (HRMS) (Sica et al 2015) (Fig.…”
Section: Mb 817996supporting
confidence: 72%
See 2 more Smart Citations
“…5), were isolated and identified based on comparison of their retention times and HRESIMS and MS/MS fragmentation patterns to standards in our in-house database (El-Elimat et al 2013). The NMR data for the compounds were also consistent with those reported in the literature (Hegde et al 1998(Hegde et al , 2001El-Elimat et al 2017). Additionally, the same compounds were identified in cultures of G618, G833, and G834, all grown on PDA, and analyzed by in situ sampling analysis using a droplet-LMJ-SSP coupled to an UPLC-high-resolution mass spectrometry (HRMS) (Sica et al 2015) (Fig.…”
Section: Mb 817996supporting
confidence: 72%
“…Additionally, 2 was recently isolated from an unidentified coprophilous fungus belonging to the Pleosporaceae, along with other closely related cyclodepsipeptides (Isaka et al 2014). Both compounds have been described to have selective inhibition against human NK2 receptors (Hegde et al 1998(Hegde et al , 2001, and 2 exhibited antimalarial activity against Plasmodium falciparum K1 (Isaka et al 2014). Compounds 1 and 2 were also tested for antimicrobial and cytotoxicity in this study, but no significant inhibitions were observed.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…SCH217048 (Fig. 42) was isolated from an unidentified fungal culture at Schering-Plough [124]. The culture sample was collected from a Sri Lankan forest.…”
Section: Li-f Antibioticsmentioning
confidence: 99%
“…22 Other bioactive fungal cyclodepsipeptides such as the ionophore beauvericin 23,24 and the neurokinin antagonist Sch 217048 25 have also been reported. A noteworthy structural feature of the petrosifungins is the array of the three neighboring cyclic amino acids proline and twice pipecolinic acid, which in this sequence has never been observed before in a natural cyclopeptide.…”
Section: Resultsmentioning
confidence: 99%